Exposure to potentially traumatic events in young Swiss men: associations with socio-demographics and mental health outcomes (alcohol use disorder, major depression and suicide attempts). Issue 1 (1st January 2019) - Estévez-Lamorte, Natalia; Pitzurra, Raffaela; Foster, Simon; Gmel, Gerhard; Mohler-Kuo, Meichun; Schnyder, Ulrich
ABSTRACT: Background and objective : The aims of this study were to estimate the lifetime and 12-month prevalence of exposure to potentially traumatic events (PTEs) in young men in Switzerland and to assess factors and mental health outcomes associated with such events. Method : Data were drawn from the Cohort Study on Substance Use Risk Factors (C-SURF), encompassing 5, 223 young men. Exposure to PTEs was assessed using the Post-traumatic Diagnostic Scale (PDS), Trauma History Questionnaire (THQ) and Life Event Checklist (LEC). Results : Lifetime prevalence of PTEs was 59.4%, with 37.3% reporting multiple types of events. Twelve-month prevalence was 31.2%, with 12.7% reporting multiple types of events. Low education level of participants, high maternal education, family affluence below average, and not living with biological parents were associated with a higher risk of having experienced one or more PTEs in one's lifetime. Low education level of participants and high maternal education were also related to exposure to one or more PTEs over the past 12 months. Logistic regression analyses demonstrated that PTE exposure was directly associated with all assessed mental health outcomes. The strongest relationship was found between exposure to multiple types of PTEs and suicide attempts (adjusted OR 4.9 [95% CI: 2.9–8.4]). Conclusions : These results indicate that having experienced one or multiple types of PTEs is common in Swiss young men. Efforts should be intensified to reduce exposure to PTEs and prevent and treat resulting problematic mental health outcomes in young adults.